Analisis Hukum Asas Langsung, Umum, Bebas, Rahasia, Jujur, Adil dalam Pemilihan Umum Serentak Tahun 2019 - Andi Muhammad Safwan; Samsul Wahidin; Riski Febria Nurita; Raditya Feda Rifandhana (Bhirawa Law Journal, 2021)
Based on law number 4 of 1997 article 6 regarding persons with disabilities states that there are 6 rights of persons with disabilities which include equal treatment in development and have a social role as in law number 8 of 2016 article 3 of persons with disabilities that people with disabilities lack of such capabilities have equal rights before the law. The Election Law in Indonesia specifically regulates those with disabilities and disabilities where in order to obtain their rights, the state regulates laws and regulations so that their needs can be fulfilled in participating in elections in Indonesia. Luberjurdil’s foundation is a benchmark for assessing the success of the election regulations used in this study. This research is a normative research so that it only uses bibliographical legal materials, is studied and analyzed to obtain conclusions regarding the election law that regulates voters with disabilities, especially in simultaneous elections which have high difficulties compared to the previous elections. The results of the study will ensure the achievement of Luberjurdil based on the elaboration of existing regulations whether it is properly regulated in the election laws and regulations based on the legal material obtained, which can see the fulfillment of the rights needs of voters with disabilities.